Koddaroi and xurēsitauroi in the letters of Apollonius of Tyana: new evidence for tension between Jews and Gentiles in Sardis during the Flavian period? - Penella, Robert J. (The journal of Jewish studies, 2015)
Among the letters of the sage Apollonius of Tyana, of the first century c e, are eight that berate the Sardians for their civil strife. Two of the letters refer to two Sardian groups that are at odds with one another, the Koddaroi and the Xurēsitauroi. At the core of this article is an etymological argument that Koddaroi means "the foreskinned", and that Xuresitauroi, from two Greek words meaning "shaving" and "genitals", refers not to depilation hut to the shaved look of the glans penis resulting from circumcision. If my hypothesis is correct, we have a new piece of evidence for Jewish--Gentile tensions in the first-century Diaspora in Asia Minor. I also show that my hypothesis fits well with Apollonius"s remarks in letters 39 and 40. And if my interpretation of letter 41 is correct, there is a reference there to Sardian Jews owning some Jewish slaves - which again would be a new testimony, this time on the issue of slavery among the ancient Jews.